Potensi Sinergitas Fintech Dengan Bank Syariah Dalam Meningkatkan Kinerja Perbankan Syariah Di Indonesia - Fajria, Rola Nurul (MALIA: Journal of Islamic Banking and Finance, 2019)
Technology start-ups from FinTech firms offer more convenient user experiences for example better user interfaces for the mobile management of personal finance. Besides that also lower prices and better quality for example faster speed for traditional products such as payment services. This study aims to identify and overview key risks and impact of FinTech on sharia banks in Indonesia to improving bank performance. The result of this study shows that shariah banking Indonesia needs synergy with FinTech firms to increase their performance and market share.